Barotropic tides of the Southern Indian Ocean and the Amery Ice Shelf cavity - Maraldi, Claire; Galton-Fenzi, Benjamin; Lyard, Florent; Testut, Laurent; Coleman, Richard (Geophysical Research Letters, 2007)
International audience The 8 main tidal constituents were computed using a finite element, hydrodynamic ocean tide model over the South Indian Ocean region. The discretization of the domain is of the order of 100 km over the deep ocean and a few hundred meters near the coast. Such refinement in the grid resolution enables wave propagation and damping on the continental shelves to be solved correctly. The model used the GEBCO 1-minute global bathymetric grid which was improved with updated topographic data. The model solutions show good agreement with in-situ observations and Topex-Poseidon altimeter measurements and are significantly better than previously published solutions. We obtain a combined standard deviation of 1.4 cm for differences of our new regional model against independent observations compared to about 2.5 cm for the other tide models. The greatest improvements are found around the Kerguelen Islands, around Antarctica and beneath the Amery Ice Shelf and can be explained by the high grid resolution used and the particular attention given to the accuracy of the bathymetry in those regions.